Advance-Purchase Financing of Projects with Few Buyers - Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2015)
I investigate a simple model of advance-purchase contracts as a mode of financing costly projects. The analysis can easily be reinterpreted as a model of the monopolistic provision of excludable public goods under private information. An entrepreneur has to meet some capital requirement in order to start production and sell the related good to a limited number of potential buyers who are privately informed about their willingness to pay. I find that advance-purchase arrangements enable more costly projects to be financed than traditional funding sources. The entrepreneur is able to use advance-purchase surcharges as a price discrimination device. However, the discriminatory power is limited by the problem of free-riding, which is exacerbated as the number of potential buyers increases. I apply the model to research and development activities in the health industry, discussing the availability of new drugs and vaccines in poor countries.
Keywords: D42; G32; H41; L12; L26; O31; 330; pre-ordering; price discrimination; excludable public goods; monopolistic provision; crowdfunding; innovation and R&D